2020
DOI: 10.3390/sym12040529
|View full text |Cite
|
Sign up to set email alerts
|

Navigators’ Errors in a Ship Collision via Simulation Experiment in South Korea

Abstract: A very significant number of marine accidents occur because of human errors. This study aimed to prevent ship collisions by identifying types of navigators’ errors. Based on Reason’s classification theory, the possible human errors are classified into skill-based slips (SBSs) (errors caused by the lack of skills), rule-based mistakes (RBMs) (errors caused by the misapplication of rules), and knowledge-based mistakes (KBMs) (errors caused by the lack of navigator’s knowledge). For this study, a scenario-based e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Park et al [18] presented a simulation experiment to investigate the navigators' errors in a ship collision in South Korea. The results showed that the navigators' errors were primarily due to their misjudgment of the other ship's speed and course, inadequate communication between the bridge team members, and insufficient training on collision avoidance procedures.…”
Section: The Human Elementmentioning
confidence: 99%
“…Park et al [18] presented a simulation experiment to investigate the navigators' errors in a ship collision in South Korea. The results showed that the navigators' errors were primarily due to their misjudgment of the other ship's speed and course, inadequate communication between the bridge team members, and insufficient training on collision avoidance procedures.…”
Section: The Human Elementmentioning
confidence: 99%